ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Real-time continuous measurement of tissue oxygenation (StO 2 ) can provide insight into organ transplant health and disease progression and provide feedback after medical interventions. However, existing optical oximetry approaches typically assume stable blood volume, limiting their usefulness in real-world scenarios involving vasoconstriction, vasodilation, or acute blood loss. Here, we leverage miniaturized optical sensors and Bluetooth microprocessors to create a fully implantable oximeter that measures subdermal tissue oxygenation and accounts for varying levels of blood volume. The device utilizes a wireless radiofrequency (RF) power transfer scheme that allows high bandwidth Bluetooth data transmission from three wavelength channels: green (537 nm), red (660 nm), and near-infrared (NIR) (880 nm). Results show that the addition of a green wavelength improves tissue oxygenation estimation in the presence of varying blood volumes. In silico and in vivo validation of the device and tissue oxygenation algorithm is performed in rats during hypoxia, hypercapnia, and occlusion on a variety of tissues such as paw, subdermal muscle, and kidney. Miniaturized, wireless, battery-free, implantable devices such as these that support mechanisms to compensate for varying blood volumes for StO 2 calculations offer the potential for continuous, real-time, physiologically consistent monitoring of blood hemodynamics under dynamic physiological conditions.